Resistensi Antibakteri pada Pasien Infeksi Saluran Kemih (ISK) dengan Kateterisasi Urin di Bagian Penyakit Dalam RSUD Arifin Achmad Pekanbaru - Taswin Yacob; Rita Endriani; M. Yulis Hamidy; M.Arif Budiman (Fakultas Kedokteran Universitas Riau, 2011)
Uninary tract infection (UTI) is a common health problem among the people in the world, including Indonesia.Approximately 80% of UTI in hospital are ascociated with urethral catheter used in hospitalized patients. The increaseof catheter- related UTI is olso followed by increase of antibiotic used. The diffrence in distribution of UTI causingbacteria and antibiotics resistance associated with cathetetization can change according to time and place. This stdyaims to find the pattern of antibiotic resistance in the urine of catheter related UTI patient. The research was done inDepartement of Internal Medicine RSUD arifin Achmad Pekanbaru. 31 samples were collected from hospitalizedpatient who used catheter at last 3 days and taken with indwelling catheter urine. Culture, colony count, colonyidentification and resistance test was performed by Kirby Bauer method. The result was interpretated based onClinical and Laboratory Standard Institude (CLSI). UTI found in 19 samples (61.29%), 9 samples founs no bacteria(29.03%) and Candida albicans on 3 samples (9.68%). UTI caused mostly by Gram-negative bacteria (57.89%),Gram- positive bacteria found in 42.11% of samples. The highest resistance (100%) was found on cefotaxim, cefriaxon,cefalexin and tertracyclin. The lowest resistance (73.68%) found on merofenem and co-trimoxazole.